MICROZONATION OF EARTHQUAKE HAZARD AREA USING THE HVSR METHOD IN THE SOUTHERN REGION OF KARANGASEM REGENCY - Susanti, Nova; Adawiyah, Rabiah Al; Pujaningsih, Febri Berthalita; Alrizal, Alrizal; Cipta, Athanasius (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Southern Karangasem Regency, Bali, is located in a tectonically active zone and requires detailed local scale earthquake hazard assessment. This study aims to develop an earthquake hazard microzonation map for Bungaya, Padang Kerta, Tiyingtali, and Ababi villages by integrating microtremor analysis and seismic source modeling. Single-station microtremor measurements were analyzed using the Horizontal-to-Vertical Spectral Ratio (HVSR) method to obtain dominant frequency (f0), amplification factor (A0), and seismic vulnerability index (Kg). Peak Ground Acceleration (PGA) was estimated based on modeled earthquake sources affecting the study area. The results show that f0 values range from 0.51–8.78 Hz, A0 values from 0.8–7.46, and Kg values from 0.78–14.86, indicating varying local site conditions. The estimated PGA ranges from 157 to 171 gals, corresponding to VI–VII on the MMI scale. The spatial distribution of these parameters reveals significant variation in earthquake hazard levels across the southern Karangasem region. The novelty of this study lies in the integration of HVSR-derived site response parameters with PGA modeling to produce a detailed village-scale microzonation map. The results provide valuable implications for seismic risk mitigation, spatial planning, and earthquake-resilient infrastructure development in seismically active regions.